Mengembangkan Profesionalisme Guru Pendidikan Agama Islam (PAI) Melalui Model-Model Pembelajaran - Mila Mahmudah (Jurnal Keislaman, 2021)
Learning is a systematic system consisting of various interconnected components. These components are: objectives, materials, methods and evaluation. These four components must be considered in determining learning models that will be used in learning activities. Learning models are arranged based on educational principles, psychological theories, sociology, systems analysis and other theories. Learning models can be selected, meaning that teachers can determine the learning model that will be applied in the learning process in accordance with the situation and conditions of the school environment to achieve learning objectives. Teachers are currently required to develop according to their function, fostering guiding and producing students to achieve educational goals. Curriculum development, administration and equipment facilities must be balanced with the quality of teachers in carrying out the educational process. Because in the whole process of teacher education is a major factor. So it is necessary to improve the quality and professionalism of teachers in carrying out the learning process, especially learning Islamic Religious Education where it can be through mastery of learning models, so that the learning process can develop and not be monotonous.